Language, locality, and transnational belonging: remitting the everyday practice of cultural integration. Issue 6 (25th April 2020) - Krawatzek, Félix; Sasse, Gwendolyn
ABSTRACT: This article explores how 'ordinary' German migrants in the United States reflected upon their local integration and transnational belonging with reference to their language practice in the period 1820–1970. The analysis is based on approximately 8, 000 letters sent by around 700 German-speaking migrants who wrote, over varying time periods, to family members and friends still living in their places of origin. These letters provide insights into the migrants' transnational communication networks over an extended time and from across the United States. Until the emergence of a fully centralised bureaucracy during the interwar period, most legislation affecting the living conditions of migrants varied significantly between US states. This raises the question whether the practices and narratives of belonging captured in the personal letters vary accordingly across locations, especially with regard to the balance between local and transnational belonging. Tracing this variation in sub-national destination characteristics, we argue that feelings of transnational belonging are not directly responsive to shifts in political conditions and resulting policies but rather pragmatic adaptations tailored to a particular local context. The maintenance of the German language or German community ties expressed in the letters also conveys an everyday practice of resistance or adaptation to local language policies in the US and remits concrete ideas about what it means to uphold a German identity.